Integrated management : how sustainability creates value for any business - Sroufe, Robert P. (Emerald Publishing Limited, 2025)
Today's solutions are social and technical. We have the technical feasibility; it's already in place and evolving. The social will to create new norms involves systems thinking and analytics to tackle one of the biggest opportunities of our time, "sustainable development." Integrated management comes when we realise a decision's impacts go well beyond a single bottom line and single functional perspective. Integrated management can be measured across functions, firms, and value chains in multidimensional ways. This book starts by suggesting a new vision of a performance frontier beyond using sustainability terminology. Integrated management allows us to rethink functions, enterprises, and systems dynamics to reduce waste and create value. Critical drivers and enablers provide decision-makers and policymakers with ways to take on complex problems. As larger systems-level problems are addressed and disassembled into smaller systems within systems, every enterprise can contribute to and have a vision for its own sustainable future. With the application of a strategic sustainable development framework, strategic planning, and backcasting from your vision, readers will find integrated management opportunities and manage change toward success. Integrated Management: How Sustainability Creates Value for any Business is for decision-makers and lifelong students globally who want to integrate sustainability into business strategy and management practices. Endorsed by practitioners, thought leaders, academics, and change agents, this second edition builds on the success of the first edition. It includes more evidence of integration already underway at multinational companies' operational, tactical, and strategic level practices. Within each chapter, readers can take new highlight actions to enable change and build on best practices. The company examples, frameworks, methods, and action learning approach serve as a roadmap as you navigate across enterprises and interconnected systems to create your vision and action plan for the future.
Keywords: Management.; Sustainable development.; Industrial management.; Business & Economics -- Management.; Business and management: study and revision guides.; Management and management techniques.; elektronické knihy; electronic books